2022
DOI: 10.1186/s12883-022-03017-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac dysfunction and high-sensitive C-reactive protein are associated with troponin T elevation in ischemic stroke: insights from the SICFAIL study

Abstract: Background Troponin elevation is common in ischemic stroke (IS) patients. The pathomechanisms involved are incompletely understood and comprise coronary and non-coronary causes, e.g. autonomic dysfunction. We investigated determinants of troponin elevation in acute IS patients including markers of autonomic dysfunction, assessed by heart rate variability (HRV) time domain variables. Methods Data were collected within the Stroke Induced Cardiac FAIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
0
1
Order By: Relevance
“…[ 17 ] Following AIS, 23.6% develop AF, 10.4% develop systolic dysfunction, and 24.5% develop diastolic dysfunction. [ 18 ] The study from Adeoye et al. found that a third of 1020 adult patients with acute stroke had systolic dysfunction, highly associated with 1‐month mortality.…”
Section: Cardiovascular Dysfunction Following Aismentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17 ] Following AIS, 23.6% develop AF, 10.4% develop systolic dysfunction, and 24.5% develop diastolic dysfunction. [ 18 ] The study from Adeoye et al. found that a third of 1020 adult patients with acute stroke had systolic dysfunction, highly associated with 1‐month mortality.…”
Section: Cardiovascular Dysfunction Following Aismentioning
confidence: 99%
“…[17] Following AIS, 23.6% develop AF, 10.4% develop systolic dysfunction, and 24.5% develop diastolic dysfunction. [18] The study from Adeoye et al found that a third of 1020 adult patients with acute stroke had systolic dysfunction, highly associated with 1-month mortality. [19] Electrocardiogram (ECG) abnormalities within the initial 24 hours are frequently observed in 85% of acute stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…Дослідження SICFAIL виявили, що у значної кількості хворих з ішемічним інсультом виявляють субклінічну та клінічну картину серцевої недостатності (Heuschmann et al, 2021). З іншого боку, 5-річна частота рецидивів інсульту у пацієнтів із серцевими ускладненнями після ішемічного інсульту перевищує 50% [37,38].…”
unclassified